2019
DOI: 10.3126/jhp.v7i0.25518
|View full text |Cite
|
Sign up to set email alerts
|

Role of Health Literacy on Menstrual Hygiene Practice among the Girl Students

Abstract: The main aim of this study was to find out the role of health literacy on menstruation hygiene practice of campus girls. The population of this study were girls studying health and physical education in Surkhet Campus and HA/Staff Nurse in SEDA Campus. Surkhet was selected by proportional stratified sampling. This study followed descriptive and cross-sectional design. The study used two tools Short Test of Functional Health Literacy in Adults (S-TOFHLA) and Self Administrated Questionnaire for collecting data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…A study conducted among college female students supports that higher proportions of the adequate health-literate females have appropriate MH practices than inadequate health-literate respondents (Khanal, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…A study conducted among college female students supports that higher proportions of the adequate health-literate females have appropriate MH practices than inadequate health-literate respondents (Khanal, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the study suggests that the limited understanding of certain health concepts may be attributed to the state and scope of health education in Nepal, neglecting practical and critical aspects that link to everyday activities. The participants’ flawed understanding of concepts introduced in health education courses may result in incomplete interpretations [ 33 ]. The findings of the study conducted by Domanska et al (2018) support the conclusion that adolescents lacked familiarity with certain terms in the questionnaire and required additional practical experience in healthcare interaction and disease prevention tasks [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the findings, health literacy had no significant impact on the respondents' smoking behavior. A study showed that adequate health literate respondents are more likely to engage in healthy behavior than inadequate health literate respondents (Khanal, 2019).…”
Section: Discussionmentioning
confidence: 99%